Brittle fracture failure assessment of API 12D tanks with a semicircular-topped rectangular cleanout and stepped shell design. (August 2019) - Azzuni, Eyas; Guzey, Sukru
Abstract: The upstream segment of the oil and gas industry require temporary storage of product upon extraction, which, in turn, require adequately sized storage tanks that can withstand the operational conditions of the storage process. The American Petroleum Institute Specification 12D (API 12D) provides ten tank designs with sizes having nominal capacities ranging between 500 bbl (79.5 m 3 ) to 10, 000 bbl (1590 m 3 ). These tanks are field welded tanks that are usually produced en masse to accommodate the storage needs of the facility and the operating pressure ranges of the accompanying equipment. The brittle fracture assessment, based on API 579 using the FAD technique, is performed in this study for these ten tanks with a new extended-neck rectangular cleanout with a semicircular top that is surrounded by a reinforcement pad. This study investigated the effects of internal pressure, vacuum pressure, and hydrostatic pressure on the stresses found in the junctions connecting the roof to the top angle, the shell to the bottom plate, and the cleanout neck to the bottom plate. A finite element analysis approach was used to study the tanks by modeling them with an axisymmetric idealization, while the cleanout junction was investigated using a submodeling technique driven by a 3-D shell model of the entire tank. An elastic stress analysis was performed on the tank models, after which stress classification was carried out in each junction to assess the brittle fracture behavior. The brittle fracture assessment in a one-day mean ambient temperature of −55 °F (−48.3 °C) for each of the ten API 12D tanks is presented and discussed in this report. Highlights: Investigation of brittle fracture behavior of API 12D tanks with a new extended neck cleanout design. FEA used to determine the stresses in junctions of interest. API 579 fitness-for-service standard was used to assess the brittle fracture behavior due to stresses in the tanks. The roof-to-shell junction is prone to brittle fracture failure at a one-day mean ambient temperature of −55 °F (−48.3 °C). The shell-to-bottom junction and the cleanout junction pass the API 579 requirement for brittle fracture.